Workplace Deviant Behavior among Malaysia hotel Employees. Does organizational Factors Matter? - Alias, Mazni; Kok Wai, Chew; Ahmad, Zauwiyah; Mutalib Azim, Abdul (International Journal of Engineering and Technology, 2018)
This study aims to develop a theoretical model of the determinants of workplace deviant behaviour among Malaysia hotel employees. From our extensive reviews, we found that organisational-related factors are potential in predicting hotel employee’s deviant behaviour.  We established that organisational justice, trust in management, work autonomy, organisational constraint and organisational ethical climate as the organisational-related factors potential to influence deviant behaviour.  Practical involvements of HR professionals were recommended to support organisation in eradicating deviant behaviour at workplace.